Behavior of blackeye cowpea in the spring-summer cultivation at the Zona da Mata area of Minas Gerais State, Brazil - Vieira, Rogério Faria; Vieira, Clibas; Caldas, Marília Tiberi (Pesquisa Agropecuaria Brasileira, 2000)
Three trials involving genotypes of blackeye sorts of cowpea (Vigna unguiculata (L.) Walp.) were installed in Coimbra (Nov. 17, 1993), Ponte Nova (Nov. 19, 1993), and Viçosa (Dec. 1st, 1994), municipalities of the Zona da Mata area of Minas Gerais State, Brazil, in order to study their behavior during the spring-summer period. Yield ranged from 106 to 2,562 kg/ha. In 1993, when there was a period of three weeks of water deficit in February, maximum yields were 1,587 kg/ha in Coimbra and 1,438 kg/ha in Ponte Nova, achieved with the early-maturing and intermediary plant type line IT 87F-2687. In 1994, when rains were regular until March, maximum yield (2,562 kg/ha) was achieved with the late-maturing and semierect plant type line IT 85F-899. Brown bloch, caused by Colletotrichum falcatum f. truncata, was the only disease observed. Lines IT 85F-2687, IT 85D-3428-4, IT 83S-818, IT 83S-899, and IT 86D-716 were resistant to the fungus. The first harvest was made between 69 and 79 days after emergence, and the harvest period varied from 16 to 62 days, depending on genotype and rain period.